The effectiveness of National Service (NS): A study on perceptions of community members and staff of NS in Northernstates of Peninsular Malaysia / Muhamad Azan Yaakob, Mohd Rosli Abd Ghani and Idris Md Noor - Yaakob, Muhamad Azan; Abd Ghani, Mohd Rosli; Md Noor, Idris (Universiti Teknologi MARA, Perlis, 2017)
This study aims to evaluate the effectiveness of NS from the perspective of community members and the staff training program. Such program specifically targets trainees from the northern regions of Peninsular Malaysia (Perlis, Kedah, Penang, and northern Perak). Data were collected by interviewing the following respondents: Parents, community leaders, and the NSimplementers (coaches and facilitators). The interview focuses on general opinions of the respondents about NS, its effectiveness which includes location, content, trainers, and facilities, suggestions for improving, their perceived effects on the trainees and the community, and the entire country. A total of 56 respondents were successfully interviewed, including 21 parents, 17 community leaders, and 18 trainers. The findings revealed that majority of the interviewees agreed that the training program should be continued to develop discipline, patriotism, and nationalism. Although some of them never actually visited the camps, the interviewed parents and community leaders believed that the National Service Program provided were satisfactory level and the trainershave skills. However majority of the staff members wanted the camp infrastructure should be improved further. To improve the program, some parents suggested that NS has to deliver merit certificates which help trainees to apply for jobs. Some parents also realized that the program positively affected the trainees. Almost all community leaders suggested that the program be extended to troubled youth. They proposed the improvement of camp infrastructure and the modules of the program. In general, these findings reflect the awareness of parents, community leaders, and staff members of the importance of NS in fostering the patriotism of the younger generation.